Which antibiotic first in meningococcal disease? A national survey. Issue 4 (11th March 2011) - Hudson, L; Tickner, N; Salt, P
Abstract : Objective: Concerns over safety when using ceftriaxone in conjunction with calcium-containing solutions, despite administering these agents through different intravenous routes at different times, 1 has led to cautions from regulatory bodies.2 3 The aim of the research was to survey all paediatric units in England and Wales to ascertain current guideline and antibiotic prescribing practices for treatment of suspected meningococcal disease. Methods: In July 2009 an anonymous postal survey was sent to clinical leads of hospitals with resident acute paediatric services in England and Wales requesting information of first-line antibiotic policy for suspected meningococcal disease in children and infants. Results were collated in October 2009 and non-responding hospitals were checked for presence of a paediatric unit. In these hospitals, a consultant contact was sought and emailed a link to the same anonymous survey identical to the original. Final data was collated in November 2009. Results: 223 hospitals were identified as having acute paediatric units, from which 170 (76%) responses were received. First-line antibiotic is closely split between ceftriaxone (82 units; 48%) and cefotaxime (76 units; 45%). Ninety-six (52%) units using ceftriaxone as first line (exclusively or as either cefotaxime or ceftriaxone) have no contraindications for using it in guidelines. Only 27% of units using ceftriaxone gave age-related contra-indications, with only 14% specifically advising against use in the under 3 month age group. The vast majority of units perceived that their guidelines were adhered to within their hospital, 84 saying always (49%) and 81 saying mostly (48%), however only 61 (36%) had conducted an audit. Conclusions: First-line antibiotic choice is divided across England and Wales, with few units changing guidelines in response to the initial MHRA safety alert. Consequences of using intravenous calcium and ceftriaxone concomitantly are likely to be rare, but severe. Case reports1 of fatalities are small in number, are described in younger infants (less than 3 months) and in some cases at a significantly higher dosage of ceftriaxone than recommended by the UK product license and BNF-C. Ceftriaxone offers the advantage of a once daily administration allowing earlier ambulation and a theoretical reduction in drug error compared to the more frequently dosed cefotaxime. A compromise perhaps is found in those units who start with cefotaxime and swap to ceftriaxone if there are no contraindications. NICE guidance should provide some consistency. Over-riding this debate is the importance that any effective antibiotic is given as soon as possible in meningococcal disease and confusion about which drug should not cause delay in treatment.